Validation of the Kidney Failure Risk Equation in Kidney Transplant Recipients. (May 2020) - Tangri, Navdeep; Ferguson, Thomas W.; Wiebe, Chris; Eng, Frederick; Nash, Michelle; Astor, Brad C.; Lam, Ngan N.; Ye, Feng; Shin, Jung-Im; Whitlock, Reid; Yuen, Darren A.
Background: Predicting allograft failure in kidney transplant recipients can help plan renal replacement therapy and guide patient-provider communication. The kidney failure risk equation (KFRE) accurately predicts the need for dialysis in patients with chronic kidney disease (CKD), but has not been validated in kidney transplant recipients. Objective: We sought to validate the 4-variable KFRE (age, sex, estimated glomerular filtration rate [eGFR], and urine albumin-to-creatinine ratio [ACR]) for prediction of 2- and 5-year death-censored allograft failure. Design: Retrospective cohort study. Setting: Four independent North American Cohorts from Ontario, Canada; Alberta, Canada; Manitoba, Canada; and Wisconsin, United States, between January 1999 and December 2017. Patients: Adult kidney transplant patients at 1-year posttransplantation. Measurements: Kidney failure risk as measured by the KFRE (eGFR, urine ACR, age, and sex). Methods: We included all adult patients who had at least 1 serum creatinine and at least 1 urine ACR measurement approximately 1 year following kidney transplantation. The performance of the KFRE was evaluated using the area under the receiver operating characteristic curve (C-statistic). C-statistics from the 4 cohorts were meta-analyzed using random-effects models. Results: A total of 3659 patients were included. Pooled C-statistics were good in the entire population, at 0.81 (95% confidence interval: 0.72-0.91) for the 2-year KFRE and 0.73 (0.67-0.80) for the 5-year KFRE. Discrimination improved among patients with poorer kidney function (eGFR < 45 mL/min/1.73 m 2 ), with a C-statistic of 0.88 (0.78-0.98) for the 2-year KFRE and 0.83 (0.74-0.91) for the 5-year KFRE. Limitations: The KFRE does not predict episodes of acute rejection and there was heterogeneity between cohorts. Conclusions: The KFRE accurately predicts kidney failure in kidney transplant recipients at 1-year posttransplantation. Further validation in larger cohorts with longer follow-up times can strengthen the case for clinical implementation.